Anodic voltammetry and AFM imaging of picomoles of adriamycin adsorbed onto carbon surfaces - Brett, Ana Maria Oliveira (2002)
Adriamycin adsorbs strongly and irreversibly onto surfaces and this enabled electrochemical detection of in situ adriamycin oxidative damage to DNA. The adsorption of adriamycin onto glassy carbon and highly oriented pyrolytic graphite (HOPG) electrodes was studied by voltammetry and mode atomic force microscopy (MAC). At a glassy carbon electrode (GCE), the adsorbate has similar voltammetric behaviour to adriamycin in solution, which enabled the cyclic, differential pulse and square wave voltammetric study of the electron transfer reaction. The total surface concentration of adriamycin adsorbed onto GCE, from a 50 nM adriamycin solution during 3 min, was calculated to be 2.57×10-12 mol cm-2. The oxidation of adsorbed adriamycin is pH-dependent and corresponds to a two electron/two proton mechanism, and the detection limit for adriamycin adsorbed onto the GCE was 3.33×10-10 M. In situ AFM images show quick and spontaneous adsorption of the adriamycin onto a HOPG surface. Adriamycin forms a stable monolayer when adsorbed from different concentrations of adriamycin solutions and for short adsorption times. The strong and irreversible chemisorption of adriamycin onto carbon electrodes enables detection limits of the order of picomolar, which is much lower than the detection limits attainable by voltammetric methods for most organic compounds.